Pengendalian status gizi, kadar glukosa darah, dan tekanan darah melalui terapi gizi medis pada pasien diabetes mellitus (DM) tipe 2 rawat jalan di RSU Mataram NTB - Suhaema Suhaema; Ahmad Husain Asdie; Retno Pangastuti (Jurnal Gizi Klinik Indonesia, 2010)
Background: The prevalence of diabetes mellitus (DM) is increasing globally, including in Indonesia. Studies by Diabetes Control and Complication Trial (DCCT) and U.K. Prospective Diabetes Study Group (UKPDS) prove the benefit of medical nutrition therapy (MNT) to glycemic control. Similar studies have not been done much in Indonesia.Objective: To identify the effects of MNT to nutrient intake, control of nutrition status, blood glucose and blood pressure of type 2 DM outpatients.Method: This was a randomized controlled trial. Subject of the study consisted of 60 people. The experiment group got MNT; whereas the control group got conventional nutrition counseling. Data were processed using computer, nutrients were analyzed using nutrisurvey. Statistical t-test was done to identify the effect of intervention.Result: Intake of energy, fat and carbohydrate of the experiment group decreased signifcantly close to the necessity at subsequent decrease as much as -14.05 (p= 0. 009), -35.64 (p=0.019) and -19.14 (p=0.035). Body mass index In the experiment group decreased -0.41kg/m  and waist circumference -0.24cm, where as the control group -0.23 kg/m  and -014cm. Blood glucose level during fasting decreased -23.6 mg/dl in the experiment group and -14.03 mg/dl in the control group (p=0.036). Systolic and dyastolic blood pressure of the experiment group decreased -3.33 mmHg (p=0.035) and 2 2 -1.67 mmgHg (p=0.895), whereas the control group + 0.5 mmHg  and -1.33 mmHg; the change was insignificant.Conclusion: Intake of nutrient, nutrition status, blood glucose level and blood pressure of type 2 DM patients that got MNT was more controllable than of those that got conventional nutrition counseling.